Pembuatan Ujian Online Melalui Aplikasi Whatsapp Auto - Cecep Maulana; Suparmadi Suparmadi; Mohd Siddik (Ali Institute of Research and Publication, 2021)
In the era of covid 19, learning activities are only done using the internet that forces teachers and students to communicate with each other through applications. Whatsapp application is very familiar among children, adults and even parents because the whatsapp application is very easy to understand in its optimization and also very lightly used on android phones. It is very important to provide information for android users today, WhatsApp is one of the chat applications that are quite popular. Although there are many chat apps such as telegram, massenger and others, but WhatsApp is indeed a chat application that is easy to use and has a variety of interesting features. In making an online exam using whatsapp is not using the features in whatsapp but we use a third-party application that is whatsapp auto which is connected to the whatsapp application that we often use to chat daily both in groups and private. To obtain an effective online exam creation process, teachers must download the whatsapp auto application.